Lingkup Pertumbuhan Gereja: Memahami Hakekat, Ciri dan Tujuan Bergereja - Dinar Br Karo; Sicilia Sima (Makarios: Jurnal Teologi Kontekstual, 2023)
Church growth is an important thing that cannot be ignored, but the reality is not as expected. This is because a certain number of churches are experiencing a shift until they fall into a decline that has fatal consequences. The causal factor is the church's weakness in realizing its nature and purpose so that it is wrong in its practices, therefore a renewal of awareness is needed. The research method used in this research is a descriptive qualitative method using books, journal articles, mass media both print and online. To answer the problem of church growth, this article explains the essence, characteristics and goals of church which are useful for renewing the church's awareness to rise again from its decline and grow in accordance with God's will.